Toxicity of Glyphosate and Ethoxysulfuron to the Green Microalgae (Scenedesmus obliquus) - Burcu Ermis, U.; Demir, Nilsun (Asian Journal of Chemistry, 2010)
In this study, toxic effects of two herbicides which contain glyphosate and ethoxysulfuron for the green microalgae Scenedesmus obliquus (Turpin) Kützing were investigated and 96 h median effective concentrations (EC50) were determined. The experiments were conducted with static bioassay method by three replicates. A control group and 6 different concentrations for both herbicides (800, 400, 200, 100, 50, 25 mg L-1 for glyphosate and 8, 4, 2, 1, 0.5, 0.25 mg L-1 for ethoxysulfuron) were used. The regression equations of percentage inhibition and herbicide concentrations were calculated. The EC50 value of herbicides which contains glyphosate and ethoxysulfuron for Scenedesmus obliquus were 80.0 mg L-1 (95 % confidence interval = 47.63-118.19 mg L-1) and 1.1 mg L-1 (95% confidence interval = 0.74-1.54 mg L-1), respectively. The results indicated that the toxicity of ethoxysulfuron to Scenedesmus obliquus is 80 times more than glyphosate.